2022
DOI: 10.1111/cas.15632
|View full text |Cite
|
Sign up to set email alerts
|

BAIAP2L1 accelerates breast cancer progression and chemoresistance by activating AKT signaling through binding with ribosomal protein L3

Abstract: BAI1-associated protein 2-like 1 (BAIAP2L1), also known as insulin receptor tyrosine kinase substrate, modulates the insulin network; however, its function in breast cancer has not been explored. Immunohistochemical analysis of 140 breast cancer specimens (77 triple-negative and 63 nontriple-negative cases) indicated that BAIAP2L1 expression was higher in breast cancer tissues (56/140, 40%) than in normal breast tissues (28.3%, 15/53; p < 0.001). BAIAP2L1 expression in breast cancer was correlated with triple-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Previous research has suggested that IRTKS, as a scaffold protein, is of great importance in modulation of actin movement and cell structure [16,17]. IRTKS has also been found to play a tumor-promoting role in a variety of tumors, including hepatocellular carcinoma [11], gastric cancer [18], pancreatic cancer [19],breast cancer [20]and lung cancer [21]. In the above cancers, IRTKS is actively related to their carcinogenesis, so it is probable that IRTKS acts as an oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that IRTKS, as a scaffold protein, is of great importance in modulation of actin movement and cell structure [16,17]. IRTKS has also been found to play a tumor-promoting role in a variety of tumors, including hepatocellular carcinoma [11], gastric cancer [18], pancreatic cancer [19],breast cancer [20]and lung cancer [21]. In the above cancers, IRTKS is actively related to their carcinogenesis, so it is probable that IRTKS acts as an oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ALB in BC plasma-derived sEV is still unclear, but low expressions of ALB in serum were found to be associated with poor BC prognosis [54]. Despite the previous discovery of COL1A1 [55], EEF1A2 [56,57], and RPL3 [58] as metastasis-related proteins in BC and CSN1S1 [59], C5 [60], and C7 [61] as BC prognosis-related proteins, the function or biomarker potential of these proteins within sEVs remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…All participants provided written informed consent, and the study was conducted in accordance with the principles of the Declaration of Helsinki. Detailed descriptions of patient information have been described previously [ 40 ] and can be found in Additional file 1.…”
Section: Methodsmentioning
confidence: 99%